2011
DOI: 10.1016/j.bbmt.2010.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Superior Graft-versus-Leukemia Effect Associated with Transplantation of Haploidentical Compared with HLA-Identical Sibling Donor Grafts for High-Risk Acute Leukemia: An Historic Comparison

Abstract: The outcomes of an historic comparison of 117 consecutive, high-risk, acute leukemia patients undergoing hematopoietic stem cell transplantation (HSCT) from HLA-mismatched/haploidentical donors (HID, n = 81) or HLA-identical sibling donors (ISD, n = 36) without the use of in vitro T cell depletion (TCD), between the period of January 2005 and April 2009 were compared. Full engraftment was achieved in 98% of patients in the HID group and 97% in the ISD group. The cumulative incidences of grades II-IV acute graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 32 publications
12
101
1
1
Order By: Relevance
“…Our previous study also suggested that in patients with refractory/relapsed acute leukemia, haploidentical HSCT was associated with a lower relapse rate (26% vs 49%, P = 0.008) and better overall survival (42% vs 20%, P = 0.048) than HLA-identical sibling HSCT. 29 Kanda et al 30 reported that for standard-risk acute leukemia, the incidence of relapse after HLA-identical sibling HSCT did not significantly differ from that after haploidentical HSCT (22% vs 15%; P = 0.25); in contrast, for high-risk acute leukemia, the incidence of relapse was 47% after HLA-identical sibling HSCT versus 19% after haploidentical HSCT (P = 0.004). However, the underlying biological mechanism needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also suggested that in patients with refractory/relapsed acute leukemia, haploidentical HSCT was associated with a lower relapse rate (26% vs 49%, P = 0.008) and better overall survival (42% vs 20%, P = 0.048) than HLA-identical sibling HSCT. 29 Kanda et al 30 reported that for standard-risk acute leukemia, the incidence of relapse after HLA-identical sibling HSCT did not significantly differ from that after haploidentical HSCT (22% vs 15%; P = 0.25); in contrast, for high-risk acute leukemia, the incidence of relapse was 47% after HLA-identical sibling HSCT versus 19% after haploidentical HSCT (P = 0.004). However, the underlying biological mechanism needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…6,18,19 Furthermore, our previous study demonstrated that haplo-HSCT might be associated with a superior GVL effect than HLA-identical sibling donor grafts in high-risk acute leukemia. 20 In addition, the decreased relapse rate may be owing to some preemptive strategies for preventing relapse, such as risk-stratified DLI 10 or low-dose IL-2, 8 which is administered at our center, and early prophylactic imatinib for Phpositive ALL patients after transplantation. 7,21 The toxicity of transplantation in previous studies may explain why a reduced relapse rate did not translate to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…19 This suggests that HRD transplantations can achieve a stronger GVL effect, which may contribute to the superior survival of AML patients with unfavorable cytogenetics. Secondly, the patients in the present study all achieved CR1 through 1-2 courses of induction chemotherapy and received 2-4 courses of consolidation therapy before transplantation.…”
Section: Hrd-hsct To Treat Aml Inmentioning
confidence: 99%
“…In a historic comparison of 117 consecutive, high-risk acute leukemia patients undergoing HSCT from HLA-mismatched/haploidentical donors (HIDs; n ϭ 81) or HLA-identical sibling donors (ISDs; n ϭ 36) without in vitro T-cell depletion, Wang et al found that the 3-year OS rate was higher in HID patients (42%) than in ISD (20%) patients (P ϭ .048). 19 The investigators suggested that HID transplantations can achieve a stronger GVL effect than ISD transplantation for high-risk acute leukemia patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation